Age-related obesity and inflammaging in cats - Kobayashi, Miki; Kobayashi, Motoo (Frontiers in Veterinary Science, 2025)
Aging is characterized by chronic systemic inflammation accompanied by cellular senescence, immunosenescence, organ dysfunction, and age-related diseases. A chronic low-grade pro-inflammatory state known as “inflammaging” accelerates age-related diseases such as obesity, diabetes, vascular diseases, and certain types of cancer. Senescent cells drive age-related tissue dysfunction partially by inducing a chronic senescence-associated secretory phenotype (SASP) associated with various diseases. Obesity and insulin resistance change with advancing age and are linked to low-grade chronic inflammation, leading to age-related diseases. Obesity results in significant changes in the adipokine profile, such as reduced levels of anti-inflammatory adipokines, e.g., adiponectin. Cats are more prone to obesity than dogs owing to the unique characteristics of their glucose and lipid metabolism. Severely obese cats show excessive visceral fat accumulation, significantly increased triglyceride, free fatty acids, and TNF-α plasma concentrations as pro-inflammatory markers, and a significant decrease in adiponectin. Aged obese cats with excessive visceral fat exhibit fatty liver and enlarged adipocytes with macrophage infiltration. A healthy lifestyle is recognized as the most effective way to maintain health and fight aging. Aging is inevitable in animals; however, delaying the onset of age-related disease through adequate interventions at the early stages of SASP induction is possible. Adequate nutrition, moderate exercise, and a good mental state can effectively prevent age-related obesity in cats.